Subcluster EK2 Annotation Report - McFerrin, Harris; Bollivar, David; Gurney, Susan; Adewumi, Olubusuyi; Edgington, Nicholas; Mayoral, Jaime; Rudner, Adam; Balish, Mitchell (QUBES, 2026)
This report describes features of actinobacteriophages assigned to subcluster EK2. Additional phages may have been added to the phagesDB database since the generation of this report.
Keywords: Annotation; Feature (linguistics); Genetic data; Genome; Human genome; dept.bio